2010
DOI: 10.2174/157340310790231617
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Circulatory Support of the Critically Ill Child Awaiting Heart Transplantation

Abstract: The majority of children awaiting heart transplantation require inotropic support, mechanical ventilation, and/or extracorporeal membrane oxygenation (ECMO) support. Unfortunately, due to the limited pool of organs, many of these children do not survive to transplant. Mechanical circulatory support of the failing heart in pediatrics is a new and rapidly developing field world-wide. It is utilized in children with acute congestive heart failure associated with congenital heart disease, cardiomyopathy, and myoca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…When a pulsatile left ventricular assist device (LVAD) is used to support the blood pumping function of the damaged native heart of a patient in end-stage heart failure, it is important to consistently supply sufficient blood flow to the aorta [ 1 - 3 ]. Furthermore, it is important to reduce the variations in the physical load of the left ventricle (LV) during LVAD support because severe cardiac load variations can shorten the monophasic action potential duration of repolarization of the native heart (QT interval), thus increasing the risk of ventricular tachycardia or fibrillation [ 4 - 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…When a pulsatile left ventricular assist device (LVAD) is used to support the blood pumping function of the damaged native heart of a patient in end-stage heart failure, it is important to consistently supply sufficient blood flow to the aorta [ 1 - 3 ]. Furthermore, it is important to reduce the variations in the physical load of the left ventricle (LV) during LVAD support because severe cardiac load variations can shorten the monophasic action potential duration of repolarization of the native heart (QT interval), thus increasing the risk of ventricular tachycardia or fibrillation [ 4 - 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The anticoagulation regimen was based on protocols generally used with pediatric VADs in infants 2,16-18 . Unfractionated heparin is usually started when hemostasis has been established, with a target aPTT of 60-70 secs.…”
Section: Methodsmentioning
confidence: 99%
“…As in adults, the critical care of children with heart failure has advanced significantly with the advent of mechanical support as a bridge to transplantation. 15 The recently completed prospective trial of mechanical support in children with severe heart failure demonstrated improved survival with a pediatric ventricular assist device compared with ECMO support. 16 This, coupled with the Food and Drug Administration's approval of the Berlin Heart device for use in children and upcoming trials of other devices in smaller children, will undoubtedly increase the population of children surviving with heart failure.…”
Section: Advanced Heart Failure and Mechanical Circulatory Supportmentioning
confidence: 99%
“…Congenit Heart Dis. 2013;8: [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] These issues are also of significance in the provision of pediatric cardiac intensive care and will need to be addressed. A report by Stromberg in 2004 64 highlighted the "profound discrepancy between the current and growing need for trained pediatric cardiac intensivists and the graduation rate of these professionals from teaching programs."…”
Section: Physician Workforce Issuesmentioning
confidence: 99%